Robot‐assisted excision of rectal duplication cysts: A case report. Issue 2 (13th February 2022) - Kitazono, Masaki; Fujita, Makoto; Oyama, Tomohiro; Ikeda, Naotaka; Eguchi, Mayumi; Kamimura, Go; Sato, Rikiya; Uchiyama, Shuichiro; Toyosaki, Ryoichi; Suenaga, Toyokuni; Shimaoka, Shunji
Abstract: Rectal duplication cysts are extremely rare and account for only 4% of all gastrointestinal duplication cysts. They may become challenging for removal in the case of a large tumor in a narrow pelvis. Herein, we report a case of rectal duplication cysts excision via robotic‐assisted laparoscopic surgery and its utility. Abstract : A case of a 52‐year‐old female patient with a rectal duplication cyst is reported. Smooth and safe surgery can be expected with robot assistance when a large tumor occupies a narrow pelvis, which is difficult to operate with conventional surgery.